2022
DOI: 10.1007/s10995-022-03508-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Barriers and Facilitators to Maternal Immunization: A Systematic Narrative Synthesis of the Published Literature

Abstract: Introduction Vaccines are being developed against Group B Streptococcus and respiratory syncytial virus. These vaccines are designed to be given to pregnant women to protect infants; thus, their success depends on uptake in this population. Maternal immunization programs have struggled to achieve target coverage rates. This systematic narrative synthesis aims to define the most important barriers and facilitators for maternal immunization and to identify priority areas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…The lack of HCP recommendations to take the vaccine emerged as a high confidence barrier to adherence. This finding is consistent with other reports [111][112][113][114]. From the perspective of HCPs, the lack of recommendations is explained by anticipation of patient/parental concerns or refusal, time constraints and lack of clear guidelines and costs [115].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lack of HCP recommendations to take the vaccine emerged as a high confidence barrier to adherence. This finding is consistent with other reports [111][112][113][114]. From the perspective of HCPs, the lack of recommendations is explained by anticipation of patient/parental concerns or refusal, time constraints and lack of clear guidelines and costs [115].…”
Section: Discussionsupporting
confidence: 91%
“…[ 120 ] pointed out that clinicians and nurses are the most reliable source of vaccine information for most people. In addition, several reviews indicate HCPs as inducers of vaccination [ 112 , 113 , 117 , 121 124 ]. Trust in recommendations from health, political and religious authorities was also considered a facilitator of adherence to nonpharmaceutical measures in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Others felt that for Covid-19 vaccines, pregnant women had been made a priority far too late. Carefully framed messages should also emphasize the benefits of maternal influenza and Covid-19 vaccines for the baby [ 68 ]. We found that generally only maternal pertussis vaccines were portrayed as benefiting the infant, in keeping with a study conducted in 2018 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A literature review informed attribute and level selection. 15 Attributes were chosen with the aim of investigating vaccine-specific factors that could impact uptake. Chosen levels aimed to reflect real-life scenarios.…”
Section: Methodsmentioning
confidence: 99%